Utility of Intracardiac Echocardiography to Diagnose Infective Endocarditis - Ying Chi Yang MD; Thein Tun Aung MD, FACC; Sarah Khan; Abdul Wase MD, FACC, FACP, FHRS (SAGE Publishing, 2019)
Infective endocarditis (IE) can lead to significant morbidity and mortality without appropriate treatment. Modified Duke Criteria are accepted by many professional societies to establish the diagnosis of IE, and cardiac imaging is one of the major diagnostic criteria. Transesophageal echocardiography is an algorithmic escalation to diagnose IE when transthoracic echo does not appreciate a positive finding. In patients with contraindications to transesophageal echocardiography, cardiac magnetic resonance imaging, cardiac computed tomography (CT), cardiac CT angiography, and fluorodeoxyglucose positron emission tomography with CT or CT angiography may be alternative diagnostic tools. However, these imaging modalities have their own limitations such as local unavailability, the presence of non-magnetic resonance imaging compatible implants, or impaired renal function. Intracardiac echocardiography could be a considerable alternative under those circumstances.